Student's Academic Ethics In Using Chatgpt In Completing Arabic Language Assignments - Baiq Raudatussolihah; Ali Fathurrahman (Journal of Global Educational Perspectives, 2026)
The development of artificial intelligence technology based on generative artificial intelligence (AI) such as ChatGPT has brought significant changes in the world of higher education, including in Arabic language learning. Students of the Arabic Language Education Study Program at Makassar State University have begun utilizing ChatGPT to complete various academic assignments such as translation, writing papers, creating qawa'id, and practicing Arabic writing skills. This study aims to analyze students' academic ethics in utilizing ChatGPT in completing Arabic language assignments. The study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, documentation, and questionnaires with Arabic Language Education students at Makassar State University. The results show that the majority of students utilize ChatGPT as an academic tool to obtain references, translate vocabulary, improve Arabic sentence structure, and help understand lecture material. However, usage practices that violate academic ethics are still found, such as copy-pasting without verification, minimal citation of sources, and excessive reliance on AI. The main factors influencing ChatGPT use are ease of access, time efficiency, and the ability of AI to provide instant answers. This study concludes that the use of ChatGPT can have a positive impact on Arabic language learning if used critically, responsibly, and in accordance with the principles of academic ethics. Therefore, academic regulations and AI literacy are needed to build an honest, creative, and integrity-based academic culture in higher education environments.